Rp-hplc method development and validation for cilostazol in tablet dosage form - M. Swapna; M.Vijay Prakash; M.Sunil kumar (IJPAR JOURNAL, 2016)
A simple, precise rapid and economical reverse phase high performance liquid chromatographic method has been developed for the estimation of Rasagiline in tablet dosage from, using mobile phase containing Acetonitrile and Water in volume ratio (60 : 40 v/v) at a flow rate of 1.0 ml/min. An ODS C18 RP column (150 x 4.5 mm, 5 µ) was used as stationary phase. The linearity of Rasagiline was in the range of 5 – 25 µg/ml, shows a regression coefficient of 0.9997, quantification was done using UV detector at 265 nm. The retention time of the drug was found to be 4.61 min. The limit of detection and limit of quantification was 10.72 µg/ml and 32.49 µg/ml resp ectively. The percentage assay of Cilostazol in PLETOZ and ST1LOZ were 106.54 ± 0.663 % and 103.27 ± 0.5965 %. This proposed method is precise, accurate and rapid for determination of Cilostazol.